1987
DOI: 10.1111/j.1600-051x.1987.tb00969.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an air‐powder abrasive system on root surfaces in periodontal surgery

Abstract: The purpose of this study was to compare the effectiveness of an air-powder abrasive technique to conventional root planing during periodontal surgery. 7 patients scheduled for multiple extractions of periodontally-involved teeth were selected. Full thickness mucoperiosteal flaps were reflected, and proximal surfaces of 32 teeth were either ultrasonically scaled and exposed to the air-powder abrasive, or ultrasonically scaled and then manually root planed. Following extraction, teeth were stained for residual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
67
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(71 citation statements)
references
References 15 publications
4
67
0
Order By: Relevance
“…In our study, while it was observed a smooth appearance on half of the tooth in group applied air-flow and polishing in average, the surface roughness increased in the other half, in line with the other studies showing the harmful effects of air-polishing systems [21,23,[27][28][29]. Although polishing applications were only limited to the enamel surface in our study, this result emerged showed that air-polishing could lead to the opposite results with the philosophy of polishing application, even though it was applied on the enamel surface.…”
Section: Journal Of Biomedical Sciences Issn 2254-609xsupporting
confidence: 78%
See 1 more Smart Citation
“…In our study, while it was observed a smooth appearance on half of the tooth in group applied air-flow and polishing in average, the surface roughness increased in the other half, in line with the other studies showing the harmful effects of air-polishing systems [21,23,[27][28][29]. Although polishing applications were only limited to the enamel surface in our study, this result emerged showed that air-polishing could lead to the opposite results with the philosophy of polishing application, even though it was applied on the enamel surface.…”
Section: Journal Of Biomedical Sciences Issn 2254-609xsupporting
confidence: 78%
“…In many study, it was shown that air-polishing devices became time-saving and effective in the application on normal enamel surface [19][20][21][22][23]. However, it does not generally lead to surface modification and loss of materials to be able to be detected clinically [23,24].…”
Section: Journal Of Biomedical Sciences Issn 2254-609xmentioning
confidence: 99%
“…This damage becomes clinically relevant when APDs are repeatedly used during PMT due to its cumulative effects. [12][13][14][15][16][17][18][19][20][21][22][23][24] To minimize this problem, a novel low-abrasive air polishing powder § which allows efficient plaque removal on root cementum or dentin without root damage in vitro 25 has been developed. Since the low-abrasive powder consists of biocompatible organic salt crystals which slowly dissolve in water, it may be used for subgingival plaque removal in PMT.…”
mentioning
confidence: 99%
“…To Saad et al 29 the Robson rubber cup/brush acts more on the surface, while the bicarbonate jet technique would have more action in depth because it uses jets under controlled pressure, which are better for pit and fissure regions. Accordingly, Horning et al 8 found that the jet of sodium bicarbonate has an advantageous ability to remove plaque from hard to reach areas, such as furcations and deep grooves.…”
Section: Discussionmentioning
confidence: 99%
“…It has been used successfully in the removal of non-mineral stains caused by smoking, has been implemented indifferent components of dental implants and has been used safely in the cleaning of supragingival orthodontic devices 4,5 . However, it should be used with caution in areas of demineralized enamel because erosion of enamel prisms 6 may occur, resulting in the exposure of root surface dentin or significant substance removal 2,[7][8][9] , which is of particular interest in periodontal maintenance therapy because gingival recession is a common finding in postperiodontal treatment patients 10,11 . Sodium bicarbonate can so lead to substantial erosion or blunting of restorative materials, with the exception of ceramics, which seem to experience a less significant loss of substance 9,[12][13][14] .…”
Section: Introductionmentioning
confidence: 99%